Adjective identification in television advertisements - Abd Rahim, Normaliza (The Turkish Online Journal of Educational Technology, 2013)
Learning the Malay language has been a challenging task for foreign language learners. Learners have to learn Malay grammar structure rules in order to write simple sentences. The word choice is important in constructing a sentence. Therefore, the study focuses on the use of adjectives in television advertisements among Korean learners at Hankuk University of Foreign Studies, Korea. The objectives of the study were to identify and discuss adjectives incorporated into the advertisements. The students involved in the study were ten male and female subjects from a Malay language class. The subjects had to choose one television advertisement and view it several times. They were given three weeks to identify and discuss the adjectives in the advertisements. The subjects were interviewed on their views about the adjectives in the advertisements. The interviews were video recorded and analyzed for the purpose of the study. The results of the study revealed that each subject managed to identify five adjectives per advertisement. They also managed to offer their views on the adjectives, which were not directly uttered by the models in the advertisements. It is hoped that a future study will focus on the use of adjectives via other means of media technology.